ANALYSIS OF FACTORS AFFECTING THE FRAUD FINANCIAL STATEMENT IN TRIANGLE FRAUD PERSPECTIVE: EMPIRICAL STUDY IN MANUFACTURING COMPANIES LISTED IN INDONESIA STOCK EXCHANGE (IDX) IN 2013 – 2017 - Fathia, Fathia (International Journal of Public Budgeting, Accounting and Finance, 2019)
This study aims to analyse the effect of financial stability, external pressure, financial targets, ineffective monitoring, change in auditors, and rationalization both simultaneously and partially on financial statement fraud on manufacturing companies listed on the Indonesia Stock Exchange in 2013-2017. The research population was manufacturing companies listed on the Indonesia Stock Exchange in 2013 - 2017 as many as 98 companies. Data analysis method in this study uses Eviews program. The results of this study are that Financial Stability has a positive and significant effect on financial statement fraud. External Pressure has a positive and significant effect on financial statement fraud. Financial Target has a negative and significant effect on financial statement fraud. Ineffective Monitoring has a negative and significant effect on financial statement fraud. Change In Auditor has a negative and insignificant effect on financial statement fraud. Rationalization has a positive and significant effect on financial statement fraud. Financial Stability, External Pressure, Financial Targets, Effective Monitoring, Change In Auditors, and Rationalisation simultaneously have a significant effect on financial statement fraud variables.